Analysis Of Spare Parts Inventory Planning And Control To Improve Cost Efficiency At Pt Manunggal Jaya Makmur - Rikhi Nugroho; Tukhas Shilul Imaroh Tukhas Shilul Imaroh (Al-Makki Publisher, 2023)
PT Manunggal Jaya Makmur is one of the companies engaged in the transportation and contracting-based sector that provides integrated services from the start point to the end. In addition, it is also engaged in the repair of heavy equipment such as mixer trucks, dump trucks, colt diesel, and repair of other heavy equipment. In supporting the company's activities, PT. Manunggal Jaya Makmur implements a strategy for supplying raw materials and spare parts. In its operational activities, PT. Manunggal Jaya Makmur is still constrained by the overstock problem which ultimately causes a buildup of goods. In this study, material classification was carried out using ABC Theory analysis. Then the methods used in planning and controlling inventory management are the POQ and EOQ methods. After getting the results, the methods used during the research will be compared with the methods that have been applied so far in the company to find out the most effective methods to be applied in cost efficiency and work productivity and can maximize the profits received by the company. Based on the analysis carried out, the cost of calculating the total inventory of spare parts using the EOQ method was Rp. 205,513,000, the LFL method was Rp. 274,141,349 and the POQ method was Rp. 273,502,120. So, from these data, it can be concluded that the most optimal total cost of inventory is the EOQ method to produce greater profits and minimize overstock.